Method Comparison of two different Serological Assays for Detection of Antibodies against SARS-COV-2 in Vaccinated Individuals - Ghulam Murtaza Jamali; Sahar Iqbal; Syed Talha Naeem; Fouzia Zeeshan Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Public health has been greatly damaged by the worldwide Coronavirus Disease 2019 (COVID-19) outbreak, which was brought on by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Strong diagnostic instruments are now required in order to precisely identify and track immunity due to the pandemic. Objective: This study aimed to compare the performance of two serological assays in detecting antibodies against SARS-CoV-2 in vaccinated individuals. Methods: From August 1, 2023, to January 31, 2024, a cross-sectional study was carried out at the Dow International Medical College in Karachi, in the Section of Chemical Pathology. Analysis was done on a convenience sample of 187 laboratory employees that was non-probability. Siemens Healthineers Atellica® IM SARS-CoV-2 IgG and ROCHE Elecsys® were used to evaluate blood samples. Software for SPSS and R was used to conduct statistical studies, which included Bland-Altman plots, bivariate regression analysis, descriptive statistics, Wilcoxon signed-rank test, and Passing-Bablok regression. There was a significance threshold of p < 0.05 Results: Among all participants, 48.7% and 51.3% were tested reactive for Siemens, and Roche, respectively. Bivariate regression analyses showed weak correlations for age, gender, Covid-19 status, and vaccination status with both assays. The Bland-Altman plot demonstrated good concordance (red line at 0) between Siemens and Roche assays, though a few outliers were noted. Passing-Bablok regression analysis revealed a proportional relationship with Roche values generally higher than Siemens, but with moderate correlation. Conclusion: Both Siemens and Roche assays are reliable for detecting SARS-CoV-2 antibodies, with Roche showing slightly higher values. The findings highlight the utility of serological testing in complementing molecular diagnostics and monitoring immune responses in vaccinated individuals. Keywords: Serological assays, antibody detection, vaccination, immune response, SARS-CoV-2